Can Young Followers Drive Humanitarian Aid Via Islamic Social Funds? Insights from Muhammadiyah Zakat Institution - Munifatussaidah, Asma; Dwi Kurniawan, Bachtiar; Arbi, Dion Saputra; Agustin, Martalia Susantiana (Universitas Muhammadiyah Yogyakarta, 2025)
This research aims to observe the intention behavior of the young followers to use the payment services in Muhammadiyah Zakat Institution (LAZISMU) to donate Zakat funds as Islamic Social Finance especially for help national and global humanitarian programs, by adopting the Unified Theory of Acceptance and Use of Technology (UTAUT) Model-2. The payment services used as intermediaries for young donors with beneficiaries for humanitarian and disaster issues, such as natural disasters, hunger, and social conflict. This research used quantitative analytical methods and primary data collected through questionnaire obtained 255 respondents from Y and Z followers, in local Yogyakarta Province. Then the analysis technique is Structural Equation Model (SEM). The result of this research showed that all the variables of the Unified Theory of Acceptance and Use of Technology (UTAUT) Model-2 partially have a positive and significant effect toward young followers’ intention behaviors to pay zakat in the payment services in LAZISMU Yogyakarta. And all variables can affect the intention and use behavior of the payment services in LAZISMU moderated by the variable of Trust from young followers used payment services and digital payment in LAZISMU Yogyakarta. The present research will assist the LAZISMU as a National Islamic Philanthropy Institution in Indonesia, mapping the targets an intention and support of young donors who have accessed payment service for distributing zakat to the mustahik who is included in humanitarian, socio-economic problems, and disaster. Furthermore, this study will contribute to existing literature of Zakat through Zakat Institution.